2021
DOI: 10.1017/s0007123420000836
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Filtering: The Strategic Use of Electoral Manipulations in Russia

Abstract: Incumbents have many tools to tip elections in their favor, yet little is known about how they choose between strategies. By comparing various tactics, this article argues that electoral malpractice centered on manipulating institutions offers the greatest effectiveness while shielding incumbents from public anger and criminal prosecution. To demonstrate this, the study focuses on a widespread institutional tactic: preventing candidates from accessing the ballot. First, in survey experiments, Russian voters re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In fact, elections in Russia display almost the full menu of electoral manipulation (Schedler 2013): from restricting civil and political liberties, suppressing and controlling opposition before the election takes place, to permanently changing electoral rules, large-scale falsifications and ousting elected officials from offices. The research shows how the regime strategically uses elections at all levels to fragment and discredit the opposition, co-opt potential rivals, and manage intra-elite conflicts, as well as enhance the legitimacy (Wilson 2016;Smyth and Turovsky 2018;Szakonyi 2022;Reuter and Szakonyi 2021). Changing legislation, the regime deliberately adjusts the electoral and party law to the environmental challenges: from the very limited number of parties and proportional representation in the 2000s aimed at consolidating the dominant party system and subordinating the satellite parties (Reuter and Remington 2009;Kynev 2018), to authoritarian pluralization in the 2010s with liberalized party law combined with a mixed member majoritarian electoral system aimed at dispersing the support of satellite parties and reaching supermajority for United Russia (Wilson 2016).…”
Section: Electoral Arenamentioning
confidence: 99%
“…In fact, elections in Russia display almost the full menu of electoral manipulation (Schedler 2013): from restricting civil and political liberties, suppressing and controlling opposition before the election takes place, to permanently changing electoral rules, large-scale falsifications and ousting elected officials from offices. The research shows how the regime strategically uses elections at all levels to fragment and discredit the opposition, co-opt potential rivals, and manage intra-elite conflicts, as well as enhance the legitimacy (Wilson 2016;Smyth and Turovsky 2018;Szakonyi 2022;Reuter and Szakonyi 2021). Changing legislation, the regime deliberately adjusts the electoral and party law to the environmental challenges: from the very limited number of parties and proportional representation in the 2000s aimed at consolidating the dominant party system and subordinating the satellite parties (Reuter and Remington 2009;Kynev 2018), to authoritarian pluralization in the 2010s with liberalized party law combined with a mixed member majoritarian electoral system aimed at dispersing the support of satellite parties and reaching supermajority for United Russia (Wilson 2016).…”
Section: Electoral Arenamentioning
confidence: 99%
“…One notable example of partisan election administration comes from Ukraine, where party control of election management committees boosts that party’s vote totals by a few percentage points (Herron 2020). While outright fraud is certainly a factor in many places (Alvarez, Hall, and Hyde 2008), practices that amount to a “soft perversion of the process” are even more common, such as appointing biased poll workers (Alvarez and Hall 2006) and filtering out candidates from the opposing party (Szakonyi 2022). Independent election monitors may curtail election day fraud and violence (Asunka et al 2019), but they may simply shift fraudulent practices to earlier in the process (Daxecker 2014).…”
Section: Partisan Advantage In Local Election Administrationmentioning
confidence: 99%
“…The control group read a placebo vignette about the number of televised debates (see Table 1) (for translations, see Online Appendix B). As people may not respond similarly to different types of malpractice (Szakonyi 2021), I randomize three different types, allowing me to examine the consequences of malpractice more broadly. In all of the following analyses, I collapse all treatment groups to estimate the average treatment effect of revealing any type of malpractice.…”
Section: Experimental Vignettesmentioning
confidence: 99%
“…Previous research has found that information credibility and malpractice severity may influence how citizens perceive and respond to malfeasance information (Schedler 2013;Weitz-Shapiro and Winters 2017). Such wording has been successfully employed in similar experiments (Szakonyi 2021).…”
Section: Experimental Vignettesmentioning
confidence: 99%